PENERAPAN SANKSI ADAT KEPADA PERUSAHAAN DAN PIHAK LAIN DALAM PERADILAN ADAT - Junef, Muhar (E-Journal Widya Yustisia, 2018)
The existence of judicial custom is becoming increasingly important in the situation of countries that are not yet fully able to provide case resolution service via the formal route to remote villages. Because of that, the constitution give the recognition and tribute to the customary law along qualified: realitas, namely adat law it is alive and society; idealitas, according to the development, namely compatible with the principle of the unitary state of the republic of indonesia , and regulated in the law. The purpose of this research is to know: (1) the existence of customary courts in the judicial system of the country; and (2) form of application of sanctions the Customs on the company/the other party in violation of the provisions of the customs. The research found that: (1) the existence of judicial customary have been set in regulations perudang-undangan national although earlier through emergency act no. 1 1951 in particular the article 1 ( 2 ) letter b; continued with removal indirectly judicial village through act no. 14 year 1970 regarding basic law on judicial power; the last changed with act no. 48 / 2009 on judicial power.( 2 ) sanction inflicted on company government is in form of fines customary and companies convicted for supplying need customary and so on.